Therapeutic Implications of FABP4 in Cancer: An Emerging Target to Tackle Cancer - Sun, Naihui; Zhao, Xing (Frontiers in Pharmacology, 2022)
Metabolic reprogramming is an emerging hallmark of tumor cells. In order to survive in nutrient-deprived environment, tumor cells rewire their metabolic phenotype to provide sufficient energy and build biomass to sustain their transformed state and promote malignant behaviors. Fatty acid uptake and trafficking is an essential part of lipid metabolism within tumor cells. Fatty acid-binding proteins (FABPs), which belongs to a family of intracellular lipid-binding protein, can bind hydrophobic ligands to regulate lipid trafficking and metabolism. In particular, adipocyte fatty acid binding protein (FABP4), one of the most abundant members, has been found to be upregulated in many malignant solid tumors, and correlated with poor prognosis. In multiple tumor types, FABP4 is critical for tumor proliferation, metastasis and drug resistance. More importantly, FABP4 is a crucial driver of malignancy not only by activating the oncogenic signaling pathways, but also rewiring the metabolic phenotypes of tumor cells to satisfy their enhanced energy demand for tumor development. Thus, FABP4 serves as a tumor-promoting molecule in most cancer types, and may be a promising therapeutic target for cancer treatment.